Ergonomic Risk Factor Analysis of Musculoskeletal Disorders (MSDs) Complaints of Kurnia Lurik Sewon Bantul Workers Special Region of Yogyakarta (DIY) (Fakultas Kedokteran Universitas Gadjah Mada, 2020)
ABSTRAKBackground: Occupational safety and health (K3) in medium-sized businesses (UKM) is needed because almost 70% of SMEs in Indonesia do not know occupational safety and health (K3). Occupational diseases (PAK) in weaving workers, namely complaints of musculoskeletal disorders (MSDs) caused by unnatural work postures (clumsy) can result in disruption of skeletal muscles and high workload can affect the occurrence of loading on the muscles so that it can result in fatigue in workers because of the accumulation of lactic acid in the muscles and blood circulation resulting from the contraction process of an ergonomic work that takes place over a long period of time and repeatedly. In the lurik fabric manufacturing industry in the Bantul Special Region of Yogyakarta (DIY), namely Kurnia Lurik through the lurik fabric manufacturing process that takes place in 1.5 to 2 months that still uses non-machine looms (ATBM).Research Objectives: The purpose of this study was to analyze the risk factors for ergonomics of workers in the Kurnia Lurik Sewon Bantul Industry Special Region of Yogyakarta (DIY) against complaints of Musculoskeletal Disorders (MSDs).Research Methods: The method used in this study is a quantitative method. This type of research is a type of observational analytic study using a cross-sectional design. Assessment of work posture using the Rapid Entire Body Assessment (REBA) method, assessment of work fatigue (subjective) using the Nordic Body Map (NBM) method, measurement of lactic acid in the blood is used to measure work fatigue (objective), then reinforced by the presence of controlled variables including variables work period and duration of work in measuring Musculoskeletal Disorders (MSDs) complaints in 30 Kurnia Lurik industrial workers. The research data were analyzed and interpreted using Stata 12 statistics. Bivariate data analysis used the Chi-Square test and multivariate data analysis using the Logistic Regression test.Research Results and Discussion: The results of the study show the work posture of Kurnia Lurik workers is a risk of ergonomic danger that is the working conditions and work equipment used by workers not in accordance with the work posture of workers. Work fatigue (subjective) and work fatigue (objective) of Kurnia Lurik workers constitute risk of work environment hazards, namely the risk of hazards in the form of physical, chemical, biological, psychosocial, and ergonomic factors. Workload of Kurnia Lurik workers is a risk of danger to the worker's body that is derived from the worker's body, such as work capacity and health status of workers. Work period and duration of work of Kurnia Lurik workers constitute a risk of harm to the organization of workers and a work culture that is work risk associated with excessive workload of workers and excessive work time for workers.Conclusion: There is a risk of ergonomic hazards due to mismatch between equipment used by workers as well as working conditions with workers' body measurements. Keywords: Musculoskeletal Disorders (MSDs), Work Posture, Work Fatigue, Workload, Work Length, Work Duration